Screening isolation and biological characterization of antibacterial secondary metabolites from macrofauna endemic to the southern African coast - Njanje, Idris (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Access restricted. Expected release date in 2025.
Keywords: Uncatalogued